Dental implants an alternative for fixed prosthetic rehabilitation. - Oliveira, Maria Gabriele; Fernández, Ana María (Brazilian Journal of Implantology and Health Sciences, 2020)
The prosthetic rehabilitation of a 48-year-old male patient was performed, with the absence of 11, 14, 15 and 21 who is carrying a superior Acrylic Partial Prosthesis, which caused damage to his palate and frequently came to our service of prosthesis, in the Provincial Stomatological Teaching Clinic of Sancti Spíritus, for these difficulties. It is valued and met the necessary requirements to be implanted and thus eliminated this removable device by placing a fixed implant supported bridge. For this technique, immediately loaded Q1 unit implants were used through prosthetic rehabilitation. With this, satisfactory results were achieved for the patient, such as the comfort of its use, improving the masticatory function, increasing their self-esteem with this type of fixed rehabilitation since it provides better support and stability to their prosthetic restoration.